An Alternative Approach to Ending Economic Insecurity in Nigeria: the Role of Revolving Credit Association - Ibrahim, Saifullahi Sani (International Journal of Economics and Financial Issues, 2012)
Sustainable development is not possible when significant numbers of labour force are economically paralysed. Several policies were implemented to augment the disadvantaged populace to pave way for enable them to take the advantage of market opportunities. The major obstacles impeded government policies to recorded very little success arises from the failure to incorporate the targeted beneficiary in the design and implementation of such programme. Broader provision of financial support through credit and savings for acquisition of capital goods is crucial for effective economic management, the aim of which is to increase prosperity, equity and sustainability. The study proposed that rural dwellers should organise themselves into Credit Cooperative Societies, which could be used as Informal Financial Unit for Linkage Banking arrangement. The government (at all level) can also use these associations to channel their agricultural credit. The Credit Cooperative Societies will be used as a conduit for extending banking services to their members. This arrangement has worked in other places like Ghana and it is hoped to also work in Nigeria. Keywords: Economic insecurity; Revolving credit association; Poverty; Access to finance JEL Classifications: I390; P460